Authentic fusion / Muhammad Haziq Abdul Razak...[et al.] - Abdul Razak, Muhammad Haziq; Muhamad Zaki, Norul Hazame; Mohd Amir Hamzah, Nurul Amira; Abdul Razak, Muhammad Haziq; Muhaidar, Farhana Syahni (2015)
Authentic Fusion is a new established product that develops the spray drying process in order to produce the mixture of Kuih Cara". Our product comes in 3 different flavors that allows customer to taste different flavor of 'Kuih Cara" from its original flavor. We have identified the area that has a big potential for our product to be successful in the future. The main targets of customer are employee, housewife and also student. Every product has its own advantage and one of the advantages for our product is that we apply time consuming method in order to prepare the "Kuih Cara". Despite of that, the mixture can also be used to make waffles and muffin. We are confident that our product can attract the customer because it is easy to be prepaed and it is time consuming.